The Effect of Auditor expertise on Earnings Quality and Stock Price Synchronicity - Ali Ebrahimi Kordlar; MUSA JAVANI GHALANDARI (بررسی‌های حسابداری و حسابرسی, 2016)
In this study, we examine the effect of earnings quality on stock price synchronicity; Moreover the effect of auditor industry expertise on the effect of earnings quality on stock price synchronicity has been investigated. Stock price synchronicity is a relative measure of firm-specific information versus industry and market-wide information which have been impounded in stock price. The statistical population of study include firms listed in Tehran stock exchange and over the counter of Iran. In order to do the research, the information of 87 publicly-held companies listed in Tehran Stock Exchange and over the counter of Iran were examined as the statistical sample, by using the multivariate regression model and panel data, the analysis was done and hypothesis tested. The result of the study shows that earnings quality has significantly negative effect on stock price synchronicity and auditor industry expertise as a moderating variable intensifying earnings quality effect. In other words, auditor industry expertise via its interaction with earnings quality decreases stock price synchronicity.